Generation of thermal convection in the moss-snow layer on the coast of the Gulf of Grenfjord (West Svalbard) - P. V. Bogorodskiy; V. Yu. Kustov; V. V. Movchan; K. A. Ermokhina (Лëд и снег, 2021)
The significant part of the Arctic soils is covered by vegetation all year round, to which a layer of snow is added in winter. Both layers have a similar structure, consisting of a skeleton (organic and ice, respectively) and air-saturated pores, and, thus, form a unified system with high heat-insulating properties. But, with the temperature gradient within the layers, convection can arise, which significantly reduces the thermal resistance of the layers and affects the heat, mass and gas exchange of the atmospheric boundary layer with the ground. In this connection, the role of convective transport in the formation of the thermodynamic and biogeochemical regime of polar ecosystems becomes obvious. Note that the role of convection in the snow cover is discussed in literature, but similar studies for vegetation are absent. This is one of the reasons why the processes of heat and mass transfer in the moss-snow layer above the ground in high latitudes are reproduced in a very simplified way, even in the most advanced models of the Earth system. In this paper, we study the occurrence of instability in a system of two porous layers with heat-insulated boundaries for conditions that approximate the snow and vegetation cover of the Arctic tundra on the coast of the Gulf of Grenfjord (West Spitsbergen). The analytical solution of the Rayleigh-Darcy problem is obtained by means of expansion of the amplitudes of perturbations of vertical velocity and air temperature into series. The dependence of the convective instability threshold on the variations of the thermal physical properties of the vegetation and snow cover of the studied region, parameterized according to measurement data and literature sources, is estimated. It has been found that the stability threshold increases with growth of snow thickness and density. It was also shown that the non-Rayleigh instability becomes impossible when heated from above (meaning the long-wave mode), which occurs in a similar system of two layers of homogeneous immiscible liquids due to the difference in their thermal physical properties.